An Outside in: A Thoughtful Writing and Reading Actively with Intertextuality - Juliastuti Juliastuti (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2018)
This paper offers some concepts into what way for directions in bringing texts together. What call up our interest is curiosity to know about others writings. This brings us to intertextuality. What is intertextuality? How many types of intertextuality? How does it work in achieving an active reading and making a thoughtful writing? Texts viewed before are lacking in independent meaning, according to Kristeva, Barthes, Riffaterre, and other pioneers of the field, every text has its meaning only in relation to other texts. I refer to different genres of intertextual models and then explain these intertext’smodels in classic literatures and modern literatures terms of enhancing reading development that are the keys of mature and thoughtful writing. My findings indicate that intertextuality integrated with the abilities of the process of thinking abilities that the reading process comprises and the hallmark of mature and thoughtful writing. This means that intertextuality helps gradually mastering the forms of thought in reading and writing.